Temporal Variations in N2O Emissions in Maize and Wheat Crop Seasons: Impact of N-Fertilization, Crop Growth, and Weather Variables. Issue 1 (2nd January 2016) - Dhadli, Harmanjit S.; Brar, Babu S.; Kingra, Pavneet K.
ABSTRACT: Nitrous oxide (N2 O) emission from agricultural soils is one of the important contributors to global greenhouse gas (GHG) emissions. The impact of crop growth and weather variables on N2 O emissions during maize ( Zea mays L.) and wheat ( Triticumaestivum L.) crop seasons in unfertilized soils (TC ) and N (nitrogen) fertilized soils (TN ) was studied in a field experiment in Punjab, India. The fluxes were measured via closed chambers and a gas chromatography. In the maize crop season, N2 O fluxes in TC ranged from 11.1 to 61.2 N2 O-N g ha −1 day −1, and in TN ranged from 10.3 to 129.2 N2 O-N g ha −1 day −1, respectively, whereas in the wheat crop season fluxes were comparatively lower, and they ranged from 3.3 to 21.2 N2 O-N g ha −1 day −1 in TC and from 4.8 to 44.4 N2 O-N g ha −1 day −1 in TN . More than 60% of total season emissions occurred during vegetative growth stages of both the crops. N2 O fluxes in both crop seasons were mainly controlled by rainfall, but the impact was marked in the maize season. Additionally, the impact of fertilizer-N application on N2 O fluxes was also evident as in TN the influence of weather variables on fluxes was less by 40% than in TC . The study suggested that N2 O emissions could be large during vegetative growth stages if rainfall or irrigation events coincide with N-fertilization.